Factors influencing recurrence after surgical treatment of odontogenic maxillary sinusitis: an analysis from the oral and maxillofacial surgery point of view - Sakkas, Andreas; Weiß, Christel; Ebeling, Marcel; Pietzka, Sebastian; Wilde, Frank; Evers, Theo; Thiele, Oliver Christian; Mischkowski, Robert Andreas; Scheurer, Mario (Journal of Clinical Medicine, 2023)
The aim of the study was to determine the factors influencing the development of recurrence after the surgical treatment of odontogenic maxillary sinusitis in an oral and maxillofacial surgery clinic over a 7-year period. Demographic and anamnesis data, clinical and radiological findings, treatment and outcome were analyzed. A multivariable analysis was performed to find associations between patient age, causative focus, surgical access for sinus revision, multilayer closure with a buccal fat pad, inferior meatal antrostomy (IMA) for temporary sinus drainage and sinusitis recurrence. ...